Study about Collaborative Optimized Routing Algorithm Based Optimized and Secure Routing in WSN - Pritesh A. Patil; R. S. Deshpande (Novel Perspectives of Engineering Research Vol. 10, 2022)
In ad-hoc wireless communication, optimised routing in wireless networks is a widely discussed topic. Consistency and security issues have a substantial impact on the performance of obsolete security systems during the routing process in sensor networks. Although current routing techniques are low-cost and do not require precise placement, security remains an inescapable concern. In this research, an optimised routing technique called Collaborative Efficient Routing Algorithm (CORA) is proposed for WSN. CORA focuses on optimised data progression during routing as well as security considerations. The first phase of CORA’s operation is to identify and categorise collaborative nodes using lenient constants based on direct trust, link strength, and quality parameters. Direct trust and link strength are direct metrics, however link survival time and caused delay are taken into account when evaluating quality. The suit function is defined in the second phase for selecting the optimal nodes using the suggested CORA, which is based on direct trust, link strength, quality, and distance. In the context of selective forwarding and denial-of-service attacks, the performance of the proposed collaborative optimal routing system is evaluated using measurement metrics using a 50 dynamic nodes ad-hoc sensor network. Further this method can be explored to develop more specific optimized and robust routing mechanism to reduce this factor based on the requirements of specific applications.